Challenges of Electronic Reverse Auctions in Construction Industry—A Review - Tomáš Hanák (Economies, 2020)
The innovation of construction procurement by means of electronic reverse auctions is a controversial subject of discussion among both researchers and practitioners. This paper consolidates and critically discusses current knowledge concerning the adoption and use of electronic reverse auctions in the light of specific features of the construction industry. A systematic literature review has been employed to select papers indexed in Scopus and Web of Science databases. The findings of the study indicate that studies are addressing especially five main areas, i.e., suitability of electronic reverse auction (eRA) for construction tenders, related drivers and barriers, ethical considerations, savings potential and bidding behavior, and bid distribution. Accordingly, the authors are suggesting three directions in which future research should focus on mutual interaction of electronic reverse auctions and long-term effects on construction project outcomes.